2019
DOI: 10.31797/vetbio.506367
|View full text |Cite
|
Sign up to set email alerts
|

An unusual outcome for fetal death in bitch: a report of a case

Abstract: In this report, an unusual condition of fetal maceration conveyed with retention of fetal debris was diagnosed 5-months after breeding in a hound bitch. A five-year-old, 13 kg weighted bitch was brought to Adnan Menderes University Animal Hospital with complaints of loss of appetite and abdominal distention, five months after breeding. Although presenting a distended abdomen and mammary glands, no signs of parturition have been reported. At surgery, a reddish free intra-abdominal fluid was suctioned, and hyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Bodh et al (2014) reported the adhesions that formed with uterine rupture and they suggested that it may be seen depending on the use of oxytocin, although adhesive areas in the uterus and omentum were detected without uterine rupture in our case as reported by Sagar et al (2017). While the body temperature was within the reference values in the presented case, the pyrexia was observed in the cases Begum et al (2019) and Erdoğan et al (2019). In the presented case, the fact that its body temperature did not increase was associated with the blood parameters were in the range of normal reference values and its general condition was not yet impaired.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…Bodh et al (2014) reported the adhesions that formed with uterine rupture and they suggested that it may be seen depending on the use of oxytocin, although adhesive areas in the uterus and omentum were detected without uterine rupture in our case as reported by Sagar et al (2017). While the body temperature was within the reference values in the presented case, the pyrexia was observed in the cases Begum et al (2019) and Erdoğan et al (2019). In the presented case, the fact that its body temperature did not increase was associated with the blood parameters were in the range of normal reference values and its general condition was not yet impaired.…”
Section: Discussionsupporting
confidence: 44%
“…While it has been stated in two different case reports that the swelling and tension in the mammaries in the abdominal region were remarkable (Begum et al 2019, Erdoğan et al 2019, no swelling and tension in the mammary glands was evident in the presented case. Although no foul-smelling vaginal discharge has been reported due to the closed cervix in other cases (Begum et al 2019, Erdoğan et al 2019, mucoussmelling whitish secretion was observed in the presented case. This suggests that the cervix was open in the presented case.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Fetal retention cases at parturition have been described in the dogs having average parturition history, but the actual incidence is presumed to be low (Feldman and Nelson, 2004). Clinical findings of canine fetal retention/maceration cases are obtained from the sporadic clinical reports (Erdoğan et al, 2019;Fasulkov et al, 2014;Günzel-Apel et al, 2008;Rigau et al, 2011;Serin and Parın, 2009). The condition leads progressively (within hours or days) to uterine infection with severe postpartum metritis accompanied by fetal emphysema (Orfanau et al, 2010).…”
Section: Introductionmentioning
confidence: 99%